Expression of EZH2 is associated with poor outcome in colorectal cancer - Chen, Zhuanpeng (Oncol Lett, 2018)
Enhancer of zeste homolog 2 (EZH2), the critical component of polycomb group protein family, has been demonstrated to be overexpressed in various types of human cancer, including hepatocellular carcinoma, breast, bladder and lung cancer. The mechanism of how EZH2 promotes oncogenesis has also been well studied. However, little is known about the role of EZH2 in colorectal cancer (CRC). The main purpose of the present study was to analyze the association between EZH2 expression and the clinicopathological features of CRC. Therefore, the mRNA and protein expression levels were analyzed in tumor tissues and adjacent non-cancerous tissues by reverse transcription-quantitative polymerase chain reaction (RT-qPCR) and western blot analysis. The expression of EZH2 was demonstrated to be significantly increased in tumor tissues compared with adjacent noncancerous tissues, according to the results of western blot analysis and RT-qPCR in the majority of cases. Patients with low EZH2 expression had a longer overall survival rate compared with those with high EZH2 expression. An analysis of the association between clinicopathological features and EZH2 expression indicated that high EZH2 expression was significantly associated with tumor stage, tumor size, histological differentiation and lymph node metastasis. Multivariate analysis demonstrated that high EZH2 expression was an independent predictor of overall survival. In conclusion, to the best of our knowledge, the data presented in the present study is the first to indicate that EZH2 is upregulated in CRC and may serve as a predictor of poor outcome for patients with CRC.